REVENGE IN CHRIS MORGAN’S MOVIE FAST AND FURIOUS 7 - Ali Khaidir; Safitri Hariani (JOURNAL OF LANGUAGE, 2023)
This study is conducted to analyze revenge reflected in Fast and Furious 7 movie, and to find out the factors and the ways the antagonist’s revenge in the movie script. This study uses the theory from Baron, Byrne and Branscombe for the factors of revenge, and the theory from Mc Cullaugh for the ways how the antagonist takes the revenge. The factors of revenge analyzed in the movie script are anger (aggressiveness) and injustice. The ways of revenge being analyzed are threatening (doing terror), murdering (homicide), and aggression (attacking). The descriptive qualitative method was applied because the process of the result and discussion are accomplished descriptively. The descriptive qualitative method was applied to describe the factors and the ways the antagonist takes the revenge from the dialogue in the movie script. The results of this study show that the antagonist takes the revenge because his brother is defeated by the protagonist. The antagonist keeps giving terror to the protagonist in the movie to take the revenge.